Isolation of wild Xanthomonas strains from agricultural produce, their characterization and potential related to polysaccharide production - Gupte, M D; Kamat, M Y (Folia microbiologica, 1997)
One hundred fifty wild strains of Xanthomonas were isolated on five selective and nonselective media. The comparative effectivity of the five media has been discussed. Fifteen polysaccharide-producing strains shortlisted were identified up to species level. These were studied for polysaccharide production in shake flasks using YM media. The highest final yield of 21.3 g/L of the amount of carbon source supplied has been obtained in the optimum medium in shake-flask experiments from Xanthomonas campestris (ICa-125 strain isolated from cabbage. Rheological properties of the exocellular polysaccharide (EPS) have been compared with standard xanthan. EPS from X. campestris ICa-125 was found to be superior with respect to heat stability and effect of electrolytes as compared to standard xanthan.
Keywords: bakteriální polysacharidy; zelenina; Indie; Bacteriological Techniques; Polysaccharides, Bacterial; Culture Media; bakteriologické techniky; Vegetables; Viscosity; Xanthomonas; Food Microbiology; viskozita; kultivační média; India; potravinářská mikrobiologie